Classroom Climate, Academic Success, and Intent to Persist among Non-Christian and Christian Undergraduate Students. Issue 3 (3rd July 2019) - Craft, Christy Moran; Yang, Yang
Abstract: The purpose of this study was to examine the perceptions of classroom climate held by 3, 900 undergraduate non-Christian and Christian students at 1 large Midwestern university and to determine whether those perceptions influenced their academic success and intent to persist. The results suggested that Christian students held more positive perceptions of classroom climate than non-Christian students. Moreover, regardless of their perception of classroom climate, Christian students were more academically successful and had higher intentions to persist than non-Christian students. For all of the students in the study, positive perceptions of classroom climate advantageously impacted academic success and intent to persist.